Intensity of Thrips Attacks On Eggplant As A Result of Plant-Based Pesticides Treatment - Aif Nursyfa; Muhammad Fairuz; Aef Saefudin; Deden (Agricultural Science, 2026)
Eggplant (Solanum melongena L.) is a vegetable that is quite popular among various groups in Indonesia. Eggplant production in Indonesia in 2023 reached 699,896 tons and decreased to 675,397 tons in 2024 (BPS, 2025). With this level of productivity, eggplant plants are more susceptible to pests, one of which is Thrips. Thrips palmi usually attacks the leaves, flowers, and fruit. Damage caused by Thrips attacks on eggplant plants is characterized by silvery spots and physiological disorders on the leaves, leading to the growth of fungi that spread disease. This study was conducted in Nanggela Village, Mandirancan District, Kuningan Regency, at an altitude of ±200-300 m above sea level with a tropical climate ranging from 24°C to 33°C and an average temperature of 28°C. This study used a randomized block design (RBD) consisting of types of plant-based pesticides and their concentrations, namely clove leaf extract, garlic extract, and lemongrass extract, each of which had concentrations of 50ml/L water, 100ml/L water, and 150ml/L water. The results of the experiment showed that plant-based pesticides from garlic extract with a concentration of 100 ml/L of water had a significant effect on the intensity of attacks and damage caused by thrips, plant height, number of leaves, and crop yield in eggplant plants.